A convenient preparation of La2CuO4 from molecular precursors. (17th February 2017) - Belli Dell'Amico, Daniela; Di Giacomo, Alessio; Falchi, Lorenzo; Labella, Luca; Marelli, Marcello; Evangelisti, Claudio; Lezzerini, Marco; Marchetti, Fabio; Samaritani, Simona
Graphical abstract: By exhaustive hydrolysis of a mixture of lanthanum(III) and copper(II) carbamato complexes, La2 CuO4 was obtained via the intermediate formation of the mixed carbonate that, by thermal treatment at 600 °C, afforded the tetragonal T′ modification of the mixed oxide. The copper complex [Cu2 (O2 CNBu2 )4 (py)2 ] was structurally characterized. Abstract: Exhaustive hydrolysis of a mixture of [La4 (CO3 )(O2 CNBu2 )10 ] and [Cu(O2 CNBu2 )(py ∗ )2 ] (py ∗ = 4-dimethylamino pyridine) in molar ratio 1/2 corresponding to a La/Cu molar ratio 2/1 was carried out in toluene at room temperature. The carbamato derivatives of lanthanum and copper can be easily prepared by extraction of the metal ions from aqueous solution into heptane by the NHBu2 /CO2 system, according to a method previously reported. The copper precursor was selected amongst a number of derivatives in respect of its easy tractability. The tetragonal modification T′ of La2 CuO4 was obtained by treatment at 600 °C of the intermediate mixed carbonate. The thermal treatment of T′-La2 CuO4 at 850 °C, followed by cooling down to room temperature, afforded the orthorhombic modification of the mixed oxide.